2021
DOI: 10.1111/hel.12851
|View full text |Cite
|
Sign up to set email alerts
|

Long term impact of vonoprazan‐based Helicobacter pylori treatment on gut microbiota and its relation to post‐treatment body weight changes

Abstract: Background: Vonoprazan-based Helicobacter pylori (H. pylori) treatment is highly effective in eradicating the target bacteria; however, its post-1-year impact on gut microbiota is unknown. This study evaluated the impact of vonoprazan-based H. pylori therapy on gut microbiota 1-year post-therapy and investigated the relationship between body weight changes and post-therapy gut microbiota perturbations. Materials and Methods:Between March and May 2019, 43 patients with H. pylori infections received either vonop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
(48 reference statements)
0
13
0
1
Order By: Relevance
“…Compared with the baseline, the alpha diversities of the gut microbiota were not altered at 1 and 8 weeks after VA dual therapy 17 . Additionally, the alpha diversity was significantly increased 1 year after VA dual therapy treatment, 31 indicating that the therapy showed no influences on the gut microbiota in the short term and improved the diversity of the gut microbiota in the long term. Our previous study indicated that no alterations of the gut microbiota were induced by L‐VA dual therapy, the diversity was decreased and the microbial composition was altered immediately after H‐VA dual therapy but was restored after 1 month 32 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Compared with the baseline, the alpha diversities of the gut microbiota were not altered at 1 and 8 weeks after VA dual therapy 17 . Additionally, the alpha diversity was significantly increased 1 year after VA dual therapy treatment, 31 indicating that the therapy showed no influences on the gut microbiota in the short term and improved the diversity of the gut microbiota in the long term. Our previous study indicated that no alterations of the gut microbiota were induced by L‐VA dual therapy, the diversity was decreased and the microbial composition was altered immediately after H‐VA dual therapy but was restored after 1 month 32 .…”
Section: Discussionmentioning
confidence: 85%
“…Compared with the baseline, the alpha diversities of the gut microbiota were not altered at 1 and 8 weeks after VA dual therapy. 17 Additionally, the alpha diversity was significantly increased 1 year after VA dual therapy treatment, 31 indicating that the therapy showed no influences on the gut microbiota in the short term and improved the diversity of the gut microbiota in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…However, no differences were observed when using VA dual therapy, possibly due to the absence of clarithromycin ( Horii et al., 2021 ). One year after treatment, the alpha diversity was increased in both groups in comparison to before eradication ( Suzuki et al., 2021 ). In Japan, the duration of VA dual therapy is 7 days due to limitations by the national medical insurance policy.…”
Section: Introductionmentioning
confidence: 88%
“…Alternatively, Min Li et al [38] stated in a meta-analysis that vonoprazan instead of conventional PPI-based therapies showed significantly superior eradication rates in clarithromycin-resistant strains in both randomised controlled trials (pooled eradication rates 82.0% vs 40.0%; OR, 6.83; 95% CI, 3.63-12.86; p <0.0001) and nonrandomised controlled trials (pooled eradication rates 80.8% vs 41.8%; OR, 4.98; 95% CI, 2.47-10.03; p <0.0001). Suzuki et al [39] found that vonoprazan-based H. pylori eradication was associated with a long-term impact on gut microbiota, including effects on the richness of bacterial species. According to these studies, the choice not only of antibiotics but also of the acid suppressant may play a role in eradication success.…”
Section: Original Articlementioning
confidence: 99%